4D printing of lotus root powder gel: Color change induced by microwave. (March 2021) - Chen, Chen; Zhang, Min; Guo, Chaofan; Chen, Huizhi
Abstract: The feasibility of using microwave to stimulate the color change of curcumin lotus root gel printed by 3D was discussed. Curcumin emulsion was prepared and added into lotus root powder gel for 3D printing. The heat generated by microwave made curcumin exposed to an alkaline environment. The color change from yellow to red was realized by the deprotonation of curcumin. Mainly, the color change of the printing sample before and after the microwave treatment (MT) was measured, and the influence of the emulsion addition and the MT time on it was analyzed. The chroma of the printed sample changed after MT: L * and b * value decreased, while a * value increased. Using a variety of materials could achieve interesting color changes. The textural properties of printed sample changed significantly ( p < 0.05) after MT. Printed sample before and after microwave could provide consumers two different sensory experiences, thus contributing a new method for 4D food printing. Industrial relevance: Based on the traditional 3D printing technology, this work uses microwave as the stimulus source to realize the color change of printed product, and provides a new method for producing colorful and attractive food through 4D printing. Highlights: Stable curcumin emulsion was prepared and added into lotus root powder gel. The moisture distribution, rheological properties, and texture properties of the printing gel were analyzed. 4D printing was achieved through microwave processing of 3D printed product. Attractive composite printing was realized using materials of different formulations.